Efficient method for cyclopentanone synthesis from furfural: understanding the role of solvents and solubility in a bimetallic catalytic system - Dohade, Manisha; Dhepe, Paresh L. (Catalysis Science & Technology, 2018)
The platform chemical, furfural (FAL), is obtained from C5 stream of biomass, and effective conversion into various chemicals including cyclopentanone (CPO) would find many industrial applications. It is desirable to convert FAL to CPO under low H-2 pressure with high selectivity. In the current work, bimetallic catalysts with Pt as the base metal supported on carbon are evaluated in the synthesis of CPO using a biphasic solvent system. By tuning the solvent ratio, with toluene/water (3:4 v/v), 75% yield of CPO is achieved under 1 MPa H-2 at 180 degrees C. The difference in solubility of the substrate, intermediates and products, along with the optimum ratio of Pt and Co metals plays a crucial role in achieving better yields.